2019
DOI: 10.1007/s11695-019-04100-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Deficiencies, Bariatric Surgery, and Serum Homocysteine Level: Review of Current Literature

Abstract: Obesity is currently one of the biggest global health problems. In the case of severe obesity, bariatric surgeries are considered to be the most important method of treatment. The 2 most commonly performed bariatric surgery procedures include Roux-en-Y gastric bypass and sleeve gastrectomy. However, these methods are not free from complications, and the most common ones (moderately long or long term) are micronutrient deficiencies. The deficiency of vitamins B6, B12, and folic acid as cofactors of the folate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 73 publications
2
18
0
1
Order By: Relevance
“…Our findings are in line with other reports describing elevated plasma vitamin B6 levels in postbariatric patients upon regular multivitamin intake 16 , 18 24 , challenging the assumption that the postbariatric status per se is associated with a risk for vitamin B6 deficiency. This is supported by the observation that postbariatric vitamin B6 deficiency was mainly reported in patient collectives where a deficiency was already present before surgery 13 , 25 , 26 .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with other reports describing elevated plasma vitamin B6 levels in postbariatric patients upon regular multivitamin intake 16 , 18 24 , challenging the assumption that the postbariatric status per se is associated with a risk for vitamin B6 deficiency. This is supported by the observation that postbariatric vitamin B6 deficiency was mainly reported in patient collectives where a deficiency was already present before surgery 13 , 25 , 26 .…”
Section: Discussionsupporting
confidence: 92%
“…Folate deficiency ranges between 9% and 39% following both malabsorptive and restrictive procedures [7], being related to poor eating habits [129]. Folate deficiency can be elicited following BS due to the depletion of tissue stores as a result of inadequate dietary intake, as well as impaired absorption due to hypochlorhydria and altered intestinal pH [127].…”
Section: Folic Acidmentioning
confidence: 99%
“…Folate deficiency can be elicited following BS due to the depletion of tissue stores as a result of inadequate dietary intake, as well as impaired absorption due to hypochlorhydria and altered intestinal pH [127]. Post-surgery deficiency of folate cycle cofactors-vitamin B 6 , vitamin B 12 , and folate-is associated with increased plasma levels of homocysteine [129]. However, recent research has shown that folate may be synthetized by colonic bacteria and seems to be absorbed throughout the entire small intestine and colon, with a lowering absorption gradient from jejunum to colon.…”
Section: Folic Acidmentioning
confidence: 99%
“…Folate deficiency is associated with elevated homocysteine, cardiovascular diseases, neural tube defects, cleft lip and palate, late pregnancy complications, neurodegenerative and psychiatric disorders [ 73 – 75 ]. Elevated homocysteine levels are a risk marker for dementia, Alzheimer’s disease, bone fractures, cancers, and cardiovascular diseases [ 76 78 ]. Many studies show folate deficiency to be low due to food fortification in America [ 39 , 79 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of variant MTHFR TT has been found in 25% of Americans of Hispanic origin, 10–15% among white Americans, and only 0–1% for African Americans [ 77 , 87 – 89 ]. A review examining the nutritional deficiencies, bariatric surgery, and serum homocysteine levels found that the mutations of the MTHFR gene can be one of the reasons for persistent elevated serum homocysteine after surgery despite supplementation with B-group vitamins [ 76 ]. Knowing the presence of genetic variants of folate metabolism would provide a critical personalized care to those that might benefit from the methylated form of folic acid to prevent elevated homocysteine levels [ 76 ].…”
Section: Resultsmentioning
confidence: 99%